Subtract 2x from both sides of the equation and rewrite the remaining values.

3 + 2x
=
2x + 3

2x

2x

=

1 answer

To subtract \(2x\) from both sides of the equation \(3 + 2x = 2x + 3\), you can perform the following steps:

  1. Start with the equation: \[ 3 + 2x = 2x + 3 \]

  2. Subtract \(2x\) from both sides: \[ 3 + 2x - 2x = 2x + 3 - 2x \]

  3. Simplify both sides: \[ 3 = 3 \]

The remaining values show that both sides are equal, confirming that the equation holds true. The final expression after the operation is simply: \[ 3 = 3 \]

Similar Questions
  1. Skip to resourcesQuestion The first step to solve for y in y/3 = 6 + x is Responses A to subtract x from both sides of the
    1. answers icon 5 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions